Hygienic-sanitary quality of donated human milk in terms of the donor profile and pumping site - de Prima Souza, Ana Carolina; Rocha, Ana Carolina Lavio; Sant’Anna de Castro, Lucíola; Camargo, Bárbara Tideman Sartorio; Fogliano, Rosana Rodrigues Figueira; Tsunemi, Miriam Harumi [UNESP]; Coca, Kelly Pereira (FapUNIFESP (SciELO), 2024)
Objective: To analyze the factors associated with the hygienic-sanitary quality of donated human milk in terms of the donor profile and pumping site. Method: Cross-sectional study with retrospective data collection of records of human milk samples donated to a Human Milk Bank in São Paulo, Brazil, from 2014 to 2019. Characteristics of human milk donors, pumping site, and hygienic-sanitary quality were analyzed based on the Standards of the Brazilian Human Milk Bank Network. Results: In the hygienic-sanitary assessment, a greater presence of contamination, high acidity, and microbiological alteration were found when human milk was pumped at home and when it was donated mature. The human milk from non-exclusive donors, especially those > 30 years old, presented greater microbiological contamination and higher acidity when compared to that from exclusive donors (p < 0.05). Conclusion: Hygienic-sanitary quality impairment of donated human milk occurred when the collection was performed at home, especially among non-exclusive donors. Effective guidance and indirect supervision of donors who perform home pumping can contribute to better use of donated human milk.
Calidad higiénico-sanitaria de la leche humana donada en función del perfil del donante y lugar de extracción
Qualidade higiênico-sanitária do leite humano doado quanto ao perfil da doadora e local de extração
Keywords: Bancos de Leche Humana; Bancos de Leite Humano; Breast Milk Expression; Control de Calidad; Controle de Qualidade; Extracción de Leche Materna; Extração de Leite; Leche Humana; Leite Humano; Milk Banks; Milk, Human; Quality Control